Subclavian vein catheterisation 129 consecutive patients: infectious and mechanical complications - Lawrence, Roger A. (My University, 1995)
This thesis describes the outcome and mechanical and infectious complications of 124 subclavian catheterisations performed on 105 patients in the Medical Intensive Care Unit of Marmara University Hospital between March 1988 and December 1991. Prior to March 1988 medical staff had little experience of subclavian catheterisation and this study documents a training period when staff were first exposed to the technique. Qf the 124 catheterisations 115 were succesfully completed and remained in place for a mean of 5.2 ± 0.4 days (range half hour to 18 days) The catheter could not be placed in 3 patients. Sixty four catheters were placed by an experienced operator and 61 by inexperienced operators under supervision. No difference in complication rates was observed in procedures performed by experienced or inexperienced operators. No catheter related deaths were documented A total of 32 mechanical complications (including failure to catheterise and catheter occlusion) were seen. The most common mechanical complications were subclavian artery puncture (6) and catheter occlusion (9). Also observed were pneumothorax (2) and a variety of other complications including faulty catheter placement, bleeding from the exit site and line disruption. Catheter tip infection was documented in 25 instances on routine culture although not all of these were primary infection, 4 catheters probably having been infected by seeding from another site. Eight catheters were removed because of pyrexia and catheter sepsis documented in 5 of these. Microorganisms isolated on routine culture were Stapylococcus epidermidis, staphylococcus aureus, Klebsiella pneunoniae, Pseudomonas aureginosa, Escherichia coli and Candida albicans. The most commonly isolated organisms were Staphylococcus sp (17) Catheters infected with S aureus were in place for a significant!) shorter period of time than those infected with S epidermidis (4.9 ± 1.1 v 10 ±1.6 days: p= 0.042) and 4 of 7 catheters infected with S. aureus were removed because of pyrexia and suspicion of catheter sepsis. Catheters growing S. epidermidis remained in situ for the same period of time on average as uninfected catheters (4.9 ± 1. 1 v 5. 1 ± 0.4 days: p = 0.87).
Subklavian ven kateteri takılmış olan 124 hastadaki infeksiyon ve mekanik komplikasyonlar
Keywords: Endokrinoloji ve Metabolizma Hastalıkları; Enfeksiyon; Tıp